Using Snakes and Ladders Game and Crossword Puzzle as STAD Model Based on Students’ Creativity - Andreas Lubis; Syarifah Syarifah; Siman Siman (RIRAI Publisher, 2024)
This research analyzes and finds out several things; 1) the influence of STAD learning using the snakes and ladders game on students' social studies learning outcomes based on high and low learning activeness; 2) To determine the effect of STAD learning using TTS media on students' social studies learning outcomes based on high and low learning activeness. This research method uses quasi-experimental research (quasi-experiment). This research was divided into two classes, namely experimental class I and experimental class II, which were given learning treatment using the STAD learning model. The results of the research are that; 1) The STAD learning model using the snakes and ladders game on learning outcomes based on high learning activity of students in class V of State Elementary School, Kisaran Barat District, the average pre-test score is 65.8 and the average post-test score is 83.6 with a point difference of 18 or 26 .1%. The pre-test average was 61.8, while for Randa students' active learning the post-test average score was 71.27 with a difference of 9 points or 13.9%. 2) The STAD learning model with a crossword puzzle game on learning outcomes based on students' high learning activity, with an average pre-test score of 59.27 and after being treated the average score was 69.82, a difference of 11 points or 15.5%. Meanwhile, based on students' low learning activity, the average pre-test score was 57.33 and after being treated the average score was 67.6, the difference was 10 or 15% points. The conclusion is that there is an influence of the STAD learning model with crossword puzzles and snakes and ladders on learning outcomes based on students' high and low learning activeness and the same goes for using snakes and ladders.